(3QSGdI Edi GHf JjejIs - (3YHO Gddg Hf GdeYeGQs
(3ChdgG (B:s
(3bGd GdYHO GdabjQ YHO Gddg Hf GdeYeGQ ONdJ GdEScfOQjI GdJi ef cd OfS eUhfI hbGd GYdeJ GfGdeYQha HGHf JjejI SLhf ai SLf GdGScfOQjI s
(3BNQgG (B:s
(3hSjYde GdPjf XdehG Gi efbdH jfbdHhf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B111 - (3U(B119s
(3GfXQg eY GdeNWhW Qbe (B252s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eTgO (B/ (3cdjI GdEdgjGJ (B- (3HYKI EjQGf s
Keywords: (3GdJhMjO hGdedd hGdfMds